Intrusion Detection Systems. Model and implementation of module reacting on intrusion to computer system - Barczak, Andrzej; Bereza, Grzegorz (Studia Informatica. System and information technology, 2019)
The problems of intrusion detection capabilities are considered in this paper. The general idea of structure, model of IDS (Intrusion Detection System) and overall construction is presented with emphasize many problems which appear while creating procedures of such a tool.